DUKUNGAN KADER KESEHATAN TERHADAP KEMANDIRIAN FISIK PASIEN TUBERKULOSIS PARU - Khoiroh Umah; Meidiana Dwidiyanti; Megah Andriany (Jurnal Ilmiah Kesehatan, 2018)
Self-reliance of TB patients has an effect on the adherence to treatment in the healing process. To achieve self-reliance, patients require supports from the family and community, as well as knowledge and skills to be able to take care of themselves independently. Healthcare cadres are one form of supports that the patients need to maintain self-care capabilities. The purpose of this study was to analyze the effects of health cadres’ supports on the physical self-reliance in pulmonary TB patients. This study was a quantitative research with a pretest-posttest quasi-experimental design with the control group. The samples were 44 patients recruited using purposive sampling technique with inclusion and exclusion criteria and were assigned to two groups: intervention group (n = 22) and control group (n = 22). Instrument used modified healty card owner by Dwidiyanti. The intervention given was in the form of health cadres’ supports given for six times in six weeks. A statistical analysis using paired t-test was performed to identify the effects of the intervention on the physical self-reliance in patients with pulmonary tuberculosis. The results showed that the intervention group obtained a p-value of 0.00 and α of 0.05, where p-value < α, or p-value <0.05, indicating that there was an effect of health cadres’ supports on physical self-reliance in patients with pulmonary TB. Meanwhile, in the control group, a p-value of 0.529 and α of 0.05 were found, where p-value >α or p-value > 0.05, indicating that there was no significant difference in the patients’ physical self-reliance after given supports from the health cadres. Support interventions of health cadres improved the physical self-reliance in patients with pulmonary TB.